Development and Implementation of an Android Application for Camping Equipment Rental at Langit Adventure - Wiandra, Saka Nusi; Kalifia, Anna Dina (International Journal Software Engineering and Computer Science (IJSECS), 2024)
This study aims to develop and deploy an Android application for camping equipment rental for Langit Adventure. For the rental process that was previously carried out conventionally, this application was created to optimize it and increase efficiency, reduce chaos. Researchers use the Rapid Application Development (RAD) methodology to develop with the integration of rapid development and feedback. The results of the Black Box functional testing have been successfully met. This makes camping equipment rental easier to use and serves as a digital solution that is beneficial to renters and service providers. This application simplifies the management of camping equipment rentals, improves user experience, and provides a practical digital solution for renters and service providers.